Untersuchung der Gewitteraktivität und der relevanten großräumigen Steuerungsmechanismen über Mittel- und Westeuropa - Piper, David Amos (Wissenschaftliche Berichte des Instituts für Meteorologie und Klimaforschung des Karlsruher Instituts für Technologie, 2017)
Thunderstorm activity is characterized by a pronounced spatiotemporal variability. For several countries in Europe, this variability is analyzed and attributed to large-scale drivers using multivariate statistical methods. The analysis of atmospheric teleconnections reveals a link between the long-term behavior of thunderstorm activity and natural climate variability.